Exploring the Impact of Social Media Platforms on Secretarial Efficiency in Public Polytechnics in Southwest Nigeria - Aliu, Zainul Abideen; Olubato, Felicia Yemisi; Tijani, Saheed Abiodun; Lawal, Imran Babatunde; Tijani, Oluwafemi Muhydeen; Oyinloye, Shakirat Abolaji (International Business Education Journal, 2025)
This research examined the influence of social media platforms on the productivity of secretarial staff at Polytechnics located in Southwest Nigeria. The study was guided by three research questions. The research used a descriptive survey approach. The research population consisted of 750 secretaries employed at public Polytechnics in Southwest Nigeria. The research used a simple random sampling approach to pick a sample of 265 secretaries. A structured questionnaire was used to gather data for the research. The instrument's reliability coefficient was calculated using the Spearman rank-order correlation coefficient, resulting in a value of 0.62. The data gathered were analysed using the arithmetic mean approach. The research results indicate that social media platforms have significantly enhanced the performance of secretaries at public Polytechnics in Southwest Nigeria, resulting in increased effectiveness and efficiency in their assigned jobs. It has been determined that using social media platforms would enhance the effectiveness of secretaries by providing them with access to educational information that aligns with international standards in secretarial and management practices. The research suggested that secretaries should receive comprehensive training in using social media platforms. This training would enable them to become familiar with digital productivity platforms and tools, which are essential for enhancing managerial and administrative efficiency.